COVID‐19: Evolving challenges and opportunities for residential and vocational intellectual disability service providers. Issue 1 (23rd February 2022) - Trip, Henrietta; Northway, Ruth; Perkins, Elizabeth; Mirfin‐Veitch, Brigit; Adams, Reece
Abstract: The sustainability of service provision continues to be a challenge in the field of intellectual disability due to changes in delivery as part of intermittent or ongoing lockdown requirements during the COVID‐19 global pandemic. There are many facets to this that may have temporary or permanent impacts not only on the sector, but ultimately for service access and outcomes for people with intellectual disability themselves. This narrative literature review identifies both opportunities for, and impacts on, service providers across jurisdictions. These are explored in terms of the effects that suspension, adaptation, continuity or the cessation of service delivery have had, and those that are projected. Such impacts include, but are not limited to, changes in service access and delivery, employment roles and responsibilities, financial sustainability and the need to diversify the services and supports provided and how they are delivered. The relevance of these impacts for family carers and people with intellectual disability is also discussed. Nonetheless, there have also been opportunities which inform the shape of service delivery and pandemic planning into the future.